The applicability of Magseed® for targeted axillary dissection in breast cancer patients treated with neoadjuvant chemotherapy. (June 2021) - Reitsamer, R.; Peintinger, F.; Forsthuber, E.; Sir, A.
Abstract: Background: Targeted axillary dissection (TAD), the combination of sentinel lymph node biopsy (SLNB) and targeted lymph node biopsy (TLNB), can reduce the false negative rates of sentinel node biopsy alone dramatically in breast cancer patients, who received neoadjuvant chemotherapy (NAC). However methods for TAD are still under investigation. Methods: Magseed®, a non-radioactive magnetic marker was used to mark the biopsied positive TLN after NAC. The SLNB with the standard technetium-based method and the selective TLNB with Magseed® localization were performed in 40 patients. The TLNs were identified with the Sentimag® probe and excised in all patients. Specimen x-ray was performed to confirm the Magseed® within the prior to NAC biopsied and clipped lymph node. Results: The TLN identification rate was 100% (40/40), the SLN identification rate was 82.5% (33/40), the concordance rate between the TLN and the SLN was 65% (26/40). Complications according Magseed® deployment or identification could not be observed. Conclusion: Magseed® is a reliable and feasible marker for the identification of TLNs after NAC. Highlights: TLNB is an accurate method for the identification of marked lymph nodes after NAC. Selective excision of TLNs is feasible. Magseed® allows a non-radioactive, wireless marking of TLNs.